What do bereaved relatives of cancer patients dying in hospital want to tell us?: Analysis of free-text comments from the International Care of the Dying Evaluation (i-CODE) survey : a mixed methods approach - Gerlach, Christina; Baus, Miriam Christina; Gianicolo, Emilio A. L.; Bayer, Oliver; Haugen, Dagny Faksvåg; Weber, Martin; Mayland, Catriona R. (Supportive care in cancer, 2023)
We conducted an international survey of bereaved relatives of cancer patients dying in hospitals in seven countries, with the aim to assess and improve the quality of care. The survey used the i-CODE (International Care of the Dying Evaluation) questionnaire. Here, we report findings from the free-text comments submitted with the questionnaires. We explored for topic areas which would potentially be important for improving the quality of care. Further, we examined who reported free-texts and in what way, to reduce bias without ignoring the function the free-texts may have for those contributing.